Expression and antimicrobial activity of c-type lysozyme in taimen (Hucho taimen, Pallas). (October 2016) - Li, Shaowu; Wang, Di; Liu, Hongbai; Yin, Jiasheng; Lu, Tongyan
Abstract: Lysozymes are important defense proteins of the innate immune system and possess high antibacterial activities. In the present study, a full-length c-type lysozyme cDNA (HtLysC) was cloned and characterized from taimen ( Hucho taimen, Pallas). The cDNA contains an open reading frame (ORF) of 432 bp encoding 143 amino acid (aa), with 97% identity to LysC of Rainbow trout ( Oncorhynchus mykiss ). The amino acid sequence possessed a LYZ1 domain (16–140 aa) which contained two conserved residues (Glu 50 and Asp 67), eight conserved cysteine residues and a calcium binding site. RT-PCR analysis showed that HtLysC transcripts were most abundant in liver and less in muscle. The expression of HtLysC was up-regulated in the liver when challenged with Yersinia ruckeri . The recombinant HtLysC (rHtLysC) had lytic activities against Micrococcus lysodeikticus, Aeromonas salmonicida and Y. ruckeri . Enzyme assay showed that the optimal temperature and pH of rHtLysC were 55 °C and 6.0, respectively. Taken together, these results indicated that HtLysC might play an important role in innate immune defense against bacterial pathogens as a functional lysozyme. Highlights: A c-type lysozyme (HtLysC) from Hucho taimen was cloned and characterized. HtLysC contains a typical c-type lysozyme domain. HtLysC is constitutively expressed in the liver, intestine, blood, spleen, kidney and gill. Expression of HtLysC in the liver was up-regulated after challenged with Yersinia ruckeri . rHtLysC had lytic activities against several bacterial pathogens, including gram-positive and gram-negative bacteria.